PENGELOLAAN NEW MEDIA OLEH DINAS KESEHATAN RIAU DALAM PENYEBARAN INFORMASI COVID-19 KEPADA MASYARAKAT DI PROVINSI RIAU - Irfan Pratama; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The growing growth in the digital weorld as it grows with an age that will make people aware of the technology and media literacy, not apart from the industrial 4.0. Directly or indirectly, new media outlets are haunting the official communication patten of health with its audience. The advent of new media is having a very powerfull impact on human life right now one is using internet.The study uses a qualitative method. Research subects amounted to 3 people. Data analysis techniques by collecting data, reducing data, presenting data and drawing conclusions. As well as the technique of checking the validity of the data by extending the participation and triangulation.The results of this study are covid-19 information release by the province of Riau health service was done using platform media such as website, facebook, twiter and Instagram. The management of new media by the ministry of undrmanagement province Riau is carried out by several processes namely process organizational planning, implementation and supervision. Planning a plan consist of content, design, cost, means and time. The organization of the organization of media management by the Riau province health service has a sub human resource and is public and has are expert in managing new media are admin of graphic desaign, and it coders. Actuating is done with some are stage data collection media design and did a publication post. Controlling done with the two ways are preventive caption done before the execution began and repressive surveillance done at the end of new media management. Keywords: Management, New Media, Covid-19